Caroline Chisholm: public pedagogy personified - Peitsch , Flossie (Journal of Public Pedagogies, 2018)
This article relays stories of Caroline Chisholm’s radical intervention into life on Australia’s Victorian Goldfields. The author argues that Chisholm’s role in the cultural transformations of the period establish her as a public pedagogical pioneer influencing Australia to this day. Through her tireless engagement with the broader community, Chisholm is seen as an inspiration for public service, while inviting discussion on its challenges. The author connects this history with her own experiences as a female artist and community-based art projects that explore Chisholm’s legacy.